Job’s Suffering: A Hypostatic Cry - Moon, Catherine (Lumen et Vita, 2018)
In this essay I will examine Thomas Aquinas’ and Gustavo Gutierrez’s respective commentaries on the Book of Job. I will look into how they reconcile Job, the exemplar of unmerited suffering, back to God. First I will analyze what the two theologians understand the central question of Job to be, then I will look into how they frame this question, how they interpret the speeches and the whirlwind, and then finally what they propose the answer to the suffering of the innocent to be.